Strategic and operational considerations for the Extended Enterprise: insights from the aerospace industry - Braziotis, Christos; Tannock, James D.T.; Bourlakis, Michael (Taylor & Francis, 2017)
The Extended Enterprise (EE) paradigm has been adopted in the civil aerospace industry to enhance collaboration and product innovation among supply chain partners. Nevertheless, key aspects of this collaborative form remain poorly understood. In particular, the interrelation of strategic and operational considerations has received little attention in the literature. Our study aimed to investigate this area, using two dyads as case studies, where three companies were involved in an EE form of collaboration. The primary case company was a leading manufacturer in the civil aerospace industry that employs EE principles on both upstream and downstream sides of its supply chain. The other two case companies were key suppliers embedded in the EE. This paper aimed to develop a more complete understanding of how sharing risks and rewards results in effective collaboration among EE partners with key strategic and operational results.